2019
DOI: 10.1111/gtc.12663
|View full text |Cite
|
Sign up to set email alerts
|

RagA, an mTORC1 activator, interacts with a hedgehog signaling protein, WDR35/IFT121

Abstract: Small Ras‐like GTPases act as molecular switches for various signal transduction pathways. RagA, RagB/RagC and RagD are small Ras‐like GTPases that play regulatory roles in mTORC1. Lack of proper activation of mTORC1 can lead to diseases, such as cancer and diabetes. In this study, we found an interaction between RagA and WDR35. Mutations of WDR35 may cause genetic diseases including Sensenbrenner syndrome. WDR35 seems to be a hedgehog signaling protein with a possible ciliary function and a possible upstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Despite that RAGA is well recognized to activate mTORC1 by recruiting mTORC1 complex to the lysosome, some studies have demonstrated that RAGA might also play functions other than mTORC1 through various interaction proteins such as nucleolar protein NG132 26 , microtubule cargo adapter DYLNT 27 , and hedgehog signaling protein WDR35 28 . In this study, we identify CD47 as a new RAGA interaction protein and RAGA promotes CD47 lysosome degradation in a mTORC1-independent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite that RAGA is well recognized to activate mTORC1 by recruiting mTORC1 complex to the lysosome, some studies have demonstrated that RAGA might also play functions other than mTORC1 through various interaction proteins such as nucleolar protein NG132 26 , microtubule cargo adapter DYLNT 27 , and hedgehog signaling protein WDR35 28 . In this study, we identify CD47 as a new RAGA interaction protein and RAGA promotes CD47 lysosome degradation in a mTORC1-independent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activate amino acid-dependent mTORC1, emerging evidences have demonstrated that RAGA can also function independently of mTORC1. Some studies have demonstrated that RAGA may play functions other than mTORC1 through various interaction proteins such as nucleolar protein NG132 26 , microtubule cargo adapter DYLNT 27 , and hedgehog signaling protein WDR35 28 . Interestingly, it has been reported that RAGA expresses in microglia, the resident macrophage in the central nervous system, and is essential for the cell development and function of microglia.…”
mentioning
confidence: 99%
“…The SNP rs721932 lies in the first intron of AC079145.1 and about 1kb upstream of WDR35. The WDR35 gene, encoding a WD‐repeat protein, has been reported to be requisite for ciliary function, which plays a vital role in the transduction of signals in the hedgehog pathway 23‐26 . Recent studies have shown that this pathway was unveiled to participate in cardiovascular phenotypes, such as myocardial ischemia 27 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the interaction between RagA and WDR35 seemed to be located at the ER and not at the lysosomes. Thus, this possible dual regulation might be mediated through subcellular translocation of proteins involved in both Hh and mTORC1 signaling, in a manner mediated by RagA and WDR35 interactions [ 137 ].…”
Section: Mechanisms Leading To Hh/mtor Crosstalkmentioning
confidence: 99%